The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tnsre.2017.2771272
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Activities of Daily Living for Recovery of Upper Extremity Motor Function

Abstract: A study was conducted to investigate the effectiveness of virtual activities of daily living (ADL) practice using the SaeboVR software system for the recovery of upper extremity (UE) motor function following stroke. The system employs Kinect sensor-based tracking to translate human UE motion into the anatomical pose of the arm of the patient's avatar within a virtual environment, creating a virtual presence within a simulated task space. Patients gain mastery of 12 different integrated activities while travers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
2
30
0
3
Order By: Relevance
“…This is potentially related to the fact that VR allows creating conditions to optimize motor learning by promoting meaningful and iterative practice, together with the delivery of immediate feedback ( Levin et al, 2014 ). Although less explored, VR also provides the opportunity to integrate the practice of cognitive and/or motor activities in more ecologically valid contexts ( Rand et al, 2009 ; Faria et al, 2016a ; Adams et al, 2018 ). In such scenarios, motor training could be combined with the execution of cognitive rehabilitation tasks consisting of activities for improving cognitive domains such as attention, memory, or executive functions.…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially related to the fact that VR allows creating conditions to optimize motor learning by promoting meaningful and iterative practice, together with the delivery of immediate feedback ( Levin et al, 2014 ). Although less explored, VR also provides the opportunity to integrate the practice of cognitive and/or motor activities in more ecologically valid contexts ( Rand et al, 2009 ; Faria et al, 2016a ; Adams et al, 2018 ). In such scenarios, motor training could be combined with the execution of cognitive rehabilitation tasks consisting of activities for improving cognitive domains such as attention, memory, or executive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides wind‐ or matter‐sensing capability, the f‐TEG can be also used to monitor the motion of an arm swing, which is useful in physical rehabilitation and sport training. [ 24 ] Hand motion generates a surface flow around the e‐skin, [ 25 ] which induces a cooling sensation to the f‐TEG and thus can be detected by it without any energy requirement. Figure a shows the output response of the e‐skin to the motion of an arm swing.…”
Section: Resultsmentioning
confidence: 99%
“…J. Adams et al (2017) investigated the therapeutic influence of virtual reality training on the recovery of upper extremity functions, and found that virtual reality was related to significant clinical improvement in motor function measures in stroke patients. D. Perez-Marcos et al (2017) discovered that virtual reality system positively affected the functions of the upper extremity in moderate to severe chronic stroke patients, but this study also emphasized that the progression in the active range of motion in the upper extremity was also depends on the intensity of the training.…”
Section: Discussionmentioning
confidence: 99%